Efektivitas E-LKPD Berbasis Liveworksheet dalam Meningkatkan Hasil Belajar Sosiologi Peserta Didik di Kelas XI IPS SMA N 5 Padang - Mifta Hurrahma; Ike Sylvia (Labor Jurusan Sosiologi, Fakultas Ilmu Sosial, Universitas Negeri Padang, 2022)
This research is motivated by the low learning outcomes of students of class XI Social Sciences at SMA N 5 Padang. This study aimed to measure the effectiveness of the Liveworksheet-based LKPD in improving student learning outcomes in class XI IPS SMAN 5 Padang. This experimental study uses a quantitative approach with a one-group pretest-posttest research design. The population in this study amounted to 36 students of class XI IPS SMA N 5 Padang. The sampling technique used was total sampling with a total sample of 36 class XI IPS 1 SMA N 5 Padang students. The data collection technique uses pretest and posttest questions with a question indicator that presents a phenomenon so that students can identify the meaning of social integration and actual examples of social integration in the surrounding environment and the driving factors of social integration. The average pretest score was 52, and the average posttest score was 86. This study was analyzed using David Ausubel's meaningful learning theory. The data analysis techniques used were normality, homogeneity, and paired t-tests. Normality test and homogeneity test function as test requirements to find out whether the t-test data analysis can be continued or not. In contrast, the paired t-test is used to determine the difference between samples after and before using the live worksheet-based e-LKPD. To measure the effectiveness in this study using SPSS 22 with normality test results of 0.43, homogeneity test results of 0.68 proven sig value. > 0.05 means that the data is usually distributed and homogeneous so that the T-test can be carried out, and the T-test results are 0.00, which proves the sig value. <0.05 so that H0 is rejected, which means that there are differences in students' sociological learning outcomes. So it can be concluded that using Liveworksheet-based worksheets effectively improves student learning outcomes.